EMPOWERING COMMUNITIES: SMALL BUSINESS AND ENTREPRENEURSHIP IN DRIVING EMPLOYMENT AND INCOME GROWTH WITHIN THE SERVICE SECTOR (American Journal of Business Management, Economics and Banking, 2023)
This study delves into the pivotal role played by small businesses and private entrepreneurship within the service sector, focusing on their impact on employment generation and income augmentation for communities. Investigating the dynamic landscape of service-oriented ventures, this research explores the multifaceted contributions of small enterprises and entrepreneurial endeavours in fostering job creation and elevating the financial well-being of the populace. Through an analysis of case studies, economic models, and empirical data, this study aims to shed light on the significance of these entities in catalyzing economic growth, empowering communities, and shaping a sustainable framework for income augmentation.